2013
DOI: 10.1189/jlb.0213075
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of M1-like macrophages in type 2 diabetic islets is followed by a systemic shift in macrophage polarization

Abstract: Human T2D is characterized by a low-grade systemic inflammation, loss of ␤-cells, and diminished insulin production. Local islet immunity is still poorly understood, and hence, we evaluated macrophage subpopulations in pancreatic islets in the well-established murine model of T2D, the db/db mouse. Already at 8 weeks of disease, on average, 12 macrophages were observed in the diabetic islets, whereas only two were recorded in the nondiabetic littermates. On a detailed level, the islet resident macrophages incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 51 publications
9
106
1
1
Order By: Relevance
“…"early T2D" (Figure 3) [95]. This coincides with an increased systemic M1-like macrophage population in the spleen fuelling the systemic lowgrade inflammation by enhancing the production of IL-6, TNF-α and IL-1β.…”
Section: Islet Associated Macrophages In T2d Diabetesmentioning
confidence: 99%
See 4 more Smart Citations
“…"early T2D" (Figure 3) [95]. This coincides with an increased systemic M1-like macrophage population in the spleen fuelling the systemic lowgrade inflammation by enhancing the production of IL-6, TNF-α and IL-1β.…”
Section: Islet Associated Macrophages In T2d Diabetesmentioning
confidence: 99%
“…Egushi et al, elegantly demonstrated that during palmitate challenge, the islet immigrating macrophages to be M1-like CD11b + Ly6C high cells producing significant levels of IL-1β and TNF-α [90]. Within the diabetic islets the vast majority of the resident CD68 + F4/80 + macrophages expressed CD11b, while only 40% of the newly immigrant CD68 + F4/80 -macrophages were CD11b positive [95]. A similar frequency of Ly6C high macrophages were demonstrated in the CD68 + macrophages regardless expression of F4/80.…”
Section: Islet Associated Macrophages In T2d Diabetesmentioning
confidence: 99%
See 3 more Smart Citations